Pulsed laser deposition of aluminium-doped zinc oxide films for optoelectronics application / Reeson Kek - Reeson , Kek (2017)

(untitled)
ZnO is one of the promising materials to be used for optoelectronics due to its direct and large bandgap at 3.3 eV. Pure ZnO shows n-type behaviour but in order to increase the stability and conductivity, group III element such as B, Al and Ga can be introduced as dopants. In this project Al-doped ZnO (AZO) thin films are deposited by pulsed laser deposition (PLD) on glass and Si substrates. The project is divided into two parts. In the first part, the properties of the AZO films deposited by 355 nm and 532 nm lasers are studied. The electrical properties of AZO film are measured by four-point probe whereas the optical properties of AZO film are measured by using Ultraviolet-visible (UV-Vis) spectrophotometer. Other characterization techniques include Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) are used for measuring morphology of AZO films. The laser-produced plasma plume at different laser wavelengths and energy affects the electrical and optical properties of AZO films. By using ions probe and optical emission spectroscopy, the emission species, ions velocities and energy are obtained at different laser fluences and wavelengths. The relation of plasma characteristics and the properties of AZO thin films are discussed. In the second part, AZO thin films are deposited on p-Si (100) substrate to form AZO/Si heterojunction. The IV characteristics of the AZO/Si heterojunction are measured in dark and under illuminations. Photoresponse are observed from the AZO/Si heterojunction and the characteristics are studied.